Synergistic taste effect of MSG and 5'-IMP in pancit canton - Balba, Gina Garcia
Synergism had been known to occur between MSG (Monosodium Glutamate) and 5'-IMP (Inosine Monophosphate). This synergistic effect was studied in pancit canton for flavor enhancement or improvement. A minimum concentration of 2.5 % IMP per gram of MSG was found to enhance the flavor characteristics of the noodle as assessed by sensory evaluation tests and procedures. A One-month storage study was conducted on noodles containing 2.5 % IMP under ambient temperature (26 °C - 28 °C). Sensory Evaluation test and objective tests were done to monitor any changes in flavor that might have occurred in noodles. There was no evidence of any flavor change that might have been contributed by the nucleotides, and the flavor of noodles was found to be acceptable even after the 35th day of storage